2004
DOI: 10.1080/0363452042000299902
|View full text |Cite
|
Sign up to set email alerts
|

Group performance and collaborative technology: a longitudinal and multilevel analysis of information quality, contribution equity, and members' satisfaction in computer‐mediated groups

Abstract: This study examined changes in members' satisfaction with group processes as they worked

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Interaction in the discussion groups can change and evolve over time. Therefore, conducting observations over a relatively long period is necessary if we want to pinpoint the reasons for the change and capture the development in group processes (Flanagin et al 2004). In this respect, in the present study, students' traversion through four discussion themes was studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction in the discussion groups can change and evolve over time. Therefore, conducting observations over a relatively long period is necessary if we want to pinpoint the reasons for the change and capture the development in group processes (Flanagin et al 2004). In this respect, in the present study, students' traversion through four discussion themes was studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we considered the methodological problems that have often shown up in this kind of research: a heavy reliance on on-time observation of groups and the tension between individual-level versus group-level analyses (Flanagin et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…To perform these analyses, we used an analytical technique capable of using data from both levels of analysis (Bryk & Raudenbush, 1992; Hofmann, 1997; Hofmann, Griffin, & Gavin, 2000). Hierarchical linear modeling is becoming increasingly used in communication research (e.g., Flanagin, Park, & Seibold, 2004; Sanford, 2003) as it allows researchers to analyze data from two or more levels of analyses while accounting for the nonindependence in observations that the nested structure of multilevel data tends to produce (Klein, Dansereau, & Hall, 1994). Our analysis was conducted in Hierarchical Linear and Nonlinear Modeling (HLM) version 6.02.…”
Section: Methodsmentioning
confidence: 99%
“…Participation quality is the contribution to performance outcomes provided by an individual's interaction. It is a value measure that is concerned with the contribution that the messages sent by a team member makes to task outcomes [36]. Quality can be seen in the introduction of novel ideas or topics for consideration by the team, as well as in messages focused on task rather than unrelated social communications [37], [38].…”
Section: Input -Individual Team Member Characteristics -Cmc Anxiety mentioning
confidence: 99%